Christian Ethical Values and Their Relations to Sustainable Development in Nigeria - Jacob, Osaji Olasupo (KWASU Journal of Religious Studies, 2018)
Many states in Africa including Nigerians arc still living in confusion as a result of the influence by the Boko Haram insurgency and bankruptcy. In actual fact, today, Nigerians real capital comprises the peasant masses, thousands of jobless youths and graduates, the homeless. the armed robbers, the sick and the destitute who struggle daily for survival. Thus, the majority of the people have remained permanently marginalized by the current vicious cycle of poverty and dependency. Unfortunately, however, successive Nigerian leaders have been using religion, culture and ethnicity as an instrument of playing divide and rule game, rather than as a springboard for the inculcation and improvement of social ethical values which are fundamental to achieving correct human behaviour as it relates to productivity and nation-building. This paper, therefore, examines the place of Christian religion in the development of Nigeria with a view to generating new ideas that will contribute meaningfully to the search for democratic principles.